CD4+ T-Cells With High Common γ Chain Expression and Disturbed Cytokine Production Are Enriched in Children With Type-1 Diabetes - Seyfarth, Julia; Mütze, Nathalie; Antony Cruz, Jennifer; Kummer, Sebastian; Reinauer, Christina; Mayatepek, Ertan; Meissner, Thomas; Jacobsen, Marc (Frontiers in Immunology, 2019)
The common gamma chain (γc) contributes to the formation of different cytokine receptors (e.g. IL-2 receptor (IL-2R), IL-7R, and IL-15R), which are important for generation of self-reactive T-cells in autoimmune diseases, like in type 1 diabetes (T1D). Whereas the roles of membrane and soluble IL-2Rα and IL-7Rα variants in T1D disease pathogenesis are well described, effects of γc expression and availability for dependent receptors remain elusive. We investigated expression the of γc and dependent receptors on T-cells and soluble γc concentrations in serum from patients with T1D diabetes (n=34) and healthy controls (n=27). Effector T-cell cytokines as well as IL-2, IL-7, and IL15 induced STAT5 phosphorylation were analyzed to determine functional implications of differential γc expression of CD4+ T-cell subsets classified by t-distributed Stochastic Neighbor Embedding (t-SNE) analyses. We found increased γc and IL-7Rα expression of CD4+ T-cells from T1D patients as compared to controls. t-SNE analyses assigned differential expression to subsets of memory T-cells co-expressing γc and IL-7Rα. Whereas γc expression was positively correlated with IL-2Rα in memory T-cells from healthy controls, no dependency was found for patients with T1D. Similarly, the effector T-cell cytokine, IL-21, correlated inversely with γc expression in healthy controls, but not in T1D patients. Finally, T1D patients with high γc expression had increased proportions of IL-2 sensitive pSTAT5+ effector T-cells. These results indicated aberrantly high γc expression of T-cells from T1D patients with implications on dependent cytokine receptor signaling and effector T-cell cytokine production.